Potential Medicinal Plant Species For Fever Used by Minangkabau Ethnic at Nagari Taruang-Taruang, West Sumatra, Indonesia - Ardian Khairiah; Nisyawati Nisyawati; Marina Silalahi; Adeel Abdulkarim Fadhel Altuhaish (Al-Kauniyah: Jurnal Biologi, 2022)
AbstractFever is a symptom of illness that is commonly found in the Minangkabau ethnic community. This way, the Minangkabau ethnic community has local knowledge of utilizing plants to cure fever. The purpose of this study was to obtain species of plants used by the Minangkabau ethnic community in the treatment of diseases with symptoms of fever, as well as their potential as modern medicinal ingredients. The research method was carried out by using the open, semi-structural, and participatory observation techniques. Interviews were conducted with 9 key informants selected by purposive sampling and 126 respondents selected by snowball sampling. Data were analyzed qualitatively with descriptive statistic and quantitatively by calculating the Cultural Significance Index (CSI) and fidelity value. The medicinal plants used were 40 species from 22 families. The most used families were Euphorbiaceae (5 species), Musaceae, and Poaceae (each of 4 species), and Rubiaceae (3 species). Cocos nucifera had the highest CSI value, indicating the species was widely used in Minangkabau community. Based on the value of fidelity, 70% value was obtained by 4 plants to treat fever, namely Costus speciosus, Kalanchoe pinnata, Sacciolepeis interrupta, and Enhydra fluctuans. The four plants have the potential to be further developed into modern medicinal ingredients.AbstrakDemam merupakan gejala sakit yang umum ditemukan pada masyarakat etnis Minangkabau. Masyarakat etnis Minangkabau memiliki pengetahuan lokal dalam memanfaatkan tumbuhan untuk penyembuhan demam. Tujuan penelitian ini adalah untuk memperoleh jenis tumbuhan yang digunakan oleh masyarakat etnis Minangkabau dalam pengobatan penyakit dengan gejala demam, serta potensinya sebagai bahan obat modern. Metode penelitian dilakukan dengan teknik wawancara terbuka, semistruktural dan observasi partisipasif. Wawancara dilakukan pada 9 orang informan kunci yang dipilih secara purposive sampling dan 126 orang responden yang dipilih menggunakan snowball sampling. Data dianalisis secara statistika deskriptif dan kuantitatif dengan menghitung nilai kultural (Index of Cultural Significance) dan nilai Fidelitas. Tumbuhan yang obat yang dimanfaatkan sebanyak 40 jenis yang berasal dari 22 suku. Famili terbanyak yang dimanfaatkan yaitu Euphorbiaceae (5 jenis), Poaceae dan Musaceae (masing masing 4 jenis), dan Rubiaceae (3 jenis). Cocos nucifera merupakan tumbuhan obat dengan nilai kultural (CSI) tertinggi. Berdasarkan nilai fidelitas terdapat 4 tanaman yang memiliki nilai 70% dalam penyembuhan demam, yaitu Costus speciosus, Kalanchoe pinnata, Sacciolepeis interrupta, dan Enhydra fluctuans. Keempat tanaman tersebut memiliki potensi untuk dikembangkan menjadi bahan obat modern.